EXPLORING THE USE OF MIND MAPPING FOR LEARNING ANATOMY IN UNDERGRADUATE MEDICAL STUDENTS: A MIXED METHODS STUDY - Anam Zahra,; Zain Gulzar,; Hina Sohail,; Nimrah Fahim,; Momina Gul, (Journal of Ayub Medical College Abbottabad, 2026)
Background: Anatomy is an important preclinical subject often taught through didactic lectures to undergraduate medical students. To improve learning outcomes, mind mapping presents a promising alternative by visually organizing information and promoting active learning. The objectives of the study were to compare the effectiveness of mind mapping versus didactic lectures in improving anatomy learning and explore the experiences of undergraduate medical students with using mind mapping. Methods: A mixed-methods study was conducted involving first-year medical students at a private medical college. In the quantitative phase, test scores of first year medical students in anatomy were compared following teaching interventions involving mind mapping and didactic lectures. An independent sample t-test was used for this comparison. The qualitative phase involved three focus group discussions to explore students' experiences with using mind mapping to learn anatomy. Data were analyze inductively using Braun and Clarke's thematic analysis method. Results: The students who learned anatomy through mind mapping scored higher than those who were taught through didactic lectures. For topic 1 and 2, the p- values were 0.02 and 0.01 respectively, indicating a statistically significant difference in scores between the mind mapping and didactic lecture groups. The qualitative phase revealed five themes: Initial perceptions and expectations, Advantages of mind mapping, Limitations and improvement areas, Mind mapping versus traditional learning methods, and Recommendations. Conclusion: This study highlights mind mapping as an effective tool for improving academic performance, engagement, and collaboration in anatomy education. It demonstrates that mind mapping offers advantages over traditional teaching methods. Incorporating mind mapping into teaching practices can improve understanding of anatomical concepts and learning outcomes in medical students. Keywords: Mind mapping; Anatomy; Didactic lectures; Undergraduate medical students